Do Polls Influence Opinions? Investigating Poll Feedback Loops Using the Novel Dynamic Response Feedback Experimental Procedure. (December 2018) - Arnesen, Sveinung; Johannesson, Mikael P.; Linde, Jonas; Dahlberg, Stefan
Opinion polls may inadvertently affect public opinion, as people may change their attitudes after learning what others think. A disconcerting possibility is that opinion polls have the ability to create information cascades, wherein the majority opinion becomes increasingly larger over time. Testing poll influence on attitudes toward Syrian refugees and mandatory measles vaccination, we field survey experiments on a probability-based online survey panel. Through a novel automated procedure labeled the dynamic response feedback, we measure whether the answers from early poll respondents can influence the opinions of subsequent respondents who learn the answers of the previous respondents. Using this procedure, no feedback loops are identified.